2012
DOI: 10.1103/physrevb.85.224433
|View full text |Cite
|
Sign up to set email alerts
|

Charge and spin transport properties of Mo2X2(X= Fe,Co,Ni) molecular contacts

Abstract: We present a first-principles study of the electronic and transport properties of linear clusters Mo 2 X 2 (X = Fe,Co,Ni), formed by two X atoms separated by a nearly nonmagnetic Mo dimer, connected to gold electrodes. Density functional theory, as implemented in the SIESTA code with the generalized gradient approximation, is used to determine the spin-polarized electronic structure of the molecular contact for relaxed distances. We show that the Mo 2 X 2 clusters anchored to the gold electrodes have two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A magnetic bistability of the same kind was found by Garcı ´a-Fuente et al in the clusters Mo 2 X 2 (X = Fe, Co, Ni), formed by two X atoms separated by a nearly nonmagnetic Mo dimer. 24 These authors found that when some of those clusters form a contact between gold electrodes, the system presents spin filtering properties and magnetorresistance driven by the magnetic state of the molecular contact. Since an external magnetic field is a way to induce a change in the magnetic state of the contact, they could also act as field sensors depending on the spin-dependence of their electronic transport properties.…”
Section: Assembling Two Cr@zn 17 Unitsmentioning
confidence: 99%
“…A magnetic bistability of the same kind was found by Garcı ´a-Fuente et al in the clusters Mo 2 X 2 (X = Fe, Co, Ni), formed by two X atoms separated by a nearly nonmagnetic Mo dimer. 24 These authors found that when some of those clusters form a contact between gold electrodes, the system presents spin filtering properties and magnetorresistance driven by the magnetic state of the molecular contact. Since an external magnetic field is a way to induce a change in the magnetic state of the contact, they could also act as field sensors depending on the spin-dependence of their electronic transport properties.…”
Section: Assembling Two Cr@zn 17 Unitsmentioning
confidence: 99%
“…There are reports of a very large magnetic anisotropy for the Co-dimer 2-4 making them interesting for possible applications in future storage devices for example in combination with hexagonal carbon rings 5 . It has also been shown that Mo 2 X 2 (X = Fe,Co,Ni) clusters are able to act as a spin-filter 6 . Garcia-Fuente et al 7 computed free-standing Mo 4−x Fe x clusters and came to the conclusion that they are good candidates for molecular electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports of a very large magnetic anisotropy for the Co-dimer 2-4 making them very interesting for possible applications in future storage devices for example in combination with hexagonal carbon rings 5 . It has also been shown that Mo 2 X 2 (X = Fe,Co,Ni) are able act as a spin-filter 6 . Garcia-Fuente et al 7 computed free-standing Mo 4−x Fe x clusters and came to the conclusion that they are good candidates for molecular electronic devices.…”
Section: Introductionmentioning
confidence: 99%